Acculturating Age: Approaches to Cultural Gerontology. - Worsfold, Brian J. (Fuera de colección, 2011)
Acculturating refers to the interchange of patterns of behaviour, perceptions and ideas between groups of individuals who have different cultural backgrounds. This book, which is the result of collaboration between specialists from different disciplines from around the world, allows the comparison of systems of dependency, mediation skills, empathy and social understanding and cultural attitudes towards people who experience the stages of aging.